1990
DOI: 10.1002/arch.940140206
|View full text |Cite
|
Sign up to set email alerts
|

Effects of female wasp accessory secretions, host fat body, and host hemolymph on protein synthesis and egg viability in Microplitis croceipes (Braconidae)

Abstract: Effects of female wasp reproductive gland secretions, host fat body and hemolymph, and mechanical constriction of the parasitoid egg on protein synthesis were studied in eggs of Microplitis croceipes (Braconidae) dissected from the wasp ovary. Protein synthesis was measured by 35S-methionine incorporation in eggs held in tissue culture medium for 16 h after treatment. Synthesis was stimulated in oocytes obtained from three regions of the ovary (egg tube, reservoir, and calyx) by fat body and venom gland but no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Regardless, these results provide evidence that photoperiod may be important for in vitro growth and development of parasitoids. Greany (1986) and Ferkovich et al (1990) reported that the larvae of Microplitis crocepes and Cotesia (= Apanteles) marginiventris could not hatch until eggs reached the germband stage of development. Using our best medium, the BD-3 medium, we also found a low percentage of C. sonorensis hatched if the eggs were removed from the host prior to the formation of a germband.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, these results provide evidence that photoperiod may be important for in vitro growth and development of parasitoids. Greany (1986) and Ferkovich et al (1990) reported that the larvae of Microplitis crocepes and Cotesia (= Apanteles) marginiventris could not hatch until eggs reached the germband stage of development. Using our best medium, the BD-3 medium, we also found a low percentage of C. sonorensis hatched if the eggs were removed from the host prior to the formation of a germband.…”
Section: Discussionmentioning
confidence: 99%